IMPLEMENTASI KEBIJAKAN LAJUR KHUSUS SEPEDA SEBAGAI FASILITAS PUBLIK UNTUK MENINGKATKAN KENYAMANAN PESEPEDA DI KOTA SUKABUMI - Nopia, Nopia; Sampurna, Rizki Hegia; Mulyadi, Andi (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2023)
The infrastructure for building bicycle lanes in Indonesia has many obstacles such as the lack of bicycle enthusiasts, the use of bicycles only for certain activities, such as conducting car free days. Furthermore, there is a shortage of land on the road to build these bicycle lanes. And because it's not the main transportation. In the city of Sukabumi itself, the provision of lane infrastructure has not been realized properly, for the law that regulates it is the 2018 Raperda concerning the administration of transportation. The lanes used by cyclists are lanes specifically for bicycles and will be given space when on the road. In the city of Sukabumi, there are still many violations or dysfunctions of special bicycle lanes, thus hindering the implementation of the facilities provided to cyclists and of course it does not make cyclists comfortable if the lanes provided become dysfunctional. Data collection techniques used are observation, interviews, and documentation. Some Constraints, namely implementing agents who have constraints in implementing the policy. And the implementation of the policy is not optimal.